The impact of migration on food security in Tigray, Northern Ethiopia: The role of migration patterns and remittances - Weldemariam, Lemlem Fitwi; Sakdapolrak, Patrick; Ayanlade, Ayansina (ERDKUNDE, 2022)
Food insecurity continues to be a major international concern aggravated by the economic crisis, pandemics, violent conflicts and war. In the past decade, scholars have highlighted the role of migration in household food security, yet the interrelationships between migration and food security have shown disconnections in the literature. This study is therefore intended to provide empirical evidence of the food security–migration nexus in the case of Ethiopia’s Tigray region. Mixed-methods approaches were used in the study, including semi-structured household and expert interviews and Participatory Rural Appraisal (PRA). The study demonstrates that migration, through the flow of both financial and social remittance, has a positive impact on household food security. Based on the results, remittances contribute to household food security in a variety of ways, including facilitating the acquisition of consumable goods, diversifying sources of income, and funding the purchase of production-related inputs and health insurance, housing, and other household goals. Furthermore, the findings establish that migration is a reaction to a variety of circumstances, primarily prompted by economic factors, such as a desire to enhance one’s standard of life, high levels of poverty, high unemployment, low agricultural yields, and food crises. The study concludes that migration has dual implications for household food security: on the one hand, migration as a response strategy to food insecurity, and on the other hand, migration as a form of vulnerability to household food insecurity, demonstrating the reciprocal relationship between food security and migration.